The Sacredness of the Kolla Al-Asror Spring in the Local Wisdom of the Ujung Piring Community Bangkalan - Zaini, M (Postgraduate Studies UIN Sunan Ampel Surabaya, 2025)
This study explores the meaning and sacred value of the Kolla Al-Asror spring for its visitors. The phenomenon is significant because Kolla Al-Asror serves not only as a water source but also as a living religious symbol within the Islamic tradition of the Ujung Piring community in Bangkalan. The research focuses on two main questions: (1) What is the historical background of the Kolla Al-Asror spring? and (2) How do visitors interpret its existence? Employing a qualitative approach with descriptive analysis, data were collected through observation, interviews, and documentation to uncover the spring’s religious and social significance. The findings reveal that Kolla Al-Asror originated from the story of Syaikhona Kholil , who struck his staff into the ground, causing water to emerge miraculously. For the local community and visitors, the spring is regarded as a sacred place believed to offer both physical and spiritual healing, as well as a means to attain Barokah (divine blessing). Furthermore, the existence of Kolla Al-Asror sustains social harmony and provides inner peace for individuals seeking solutions to life’s difficulties. The pursuit of Barokah from the Waliyullah remains the central motivation for religious tourism, believed to bring safety, healing, and well-being to the faithful.